Labor mobility in the system of employment strategies of the region’s population - E. A. Kolesnik; V. S. Polovinko (Вестник университета, 2023)
The issue consideration of labor mobility as an employment strategy is relevant, because it is based on a growing understanding of the importance of labor mobility for the economic development of the country and its regions. The study purpose is to examine the place of labor mobility in the employment strategy of the population. The objectives are to study approaches to the labor mobility definition as an employment strategy, to analyze regional specifics in the labor mobility of the population, to determine the place of labor mobility in the employment strategy of the Tyumen region. General scientific, statistical and sociological methods were used in the research. The main study results are the identification of an increasing trend in the transformation of the population employment strategy and its reflection on the processes of labor mobility, grouped around changes in production and economic conditions. This provision defines not only the basis for the development of scientific discussion, but also the directions for further study of such issue.